The Influence Of Decentralization And Management Accounting Systems On Managerial Performance In An Islamic Perspective (Studi Pada PT. Pegadaian Area Lampung) - Tika Silawati; Evi Ekawati; Rosydalina Putri; Arifa Kurniawan (LP2M IAIN Palopo, 2024)
This research is quantitative research using a Casual Associative approach. This research uses data collection techniques, interviews and data processing. Primary data was obtained directly from respondents regarding managerial performance, while secondary data in the form of theories and other support was obtained from libraries, journals and previous papers.The research results show that partial decentralization has no effect on managerial performance. It can be said that the level of decentralization does not affect managerial performance in the company. The reason is because PT. Lampung Area Pegadaian does not implement a policy of granting low management authority or delegation in decision making, such as budget planning and allocation, managerial decision making, developing innovative ideas, considering large investments, and improving work quality